Evaluation of the photodegradation activity of bismuth oxoiodide/bismuth sub-carbonate nanocatalyst: Experimental design and the mechanism study - Samira Vahabirad; Alireza Nezamzadeh-Ejhieh (Ecotoxicology and Environmental Safety, 2023)
In this study, a binary BiOI/(BiO)2CO3 catalyst was prepared and used for sulfasalazine (SSZ) photodegradation in an aqueous phase. The semiconductors were identified by XRD, SEM-EDX, and UV–Vis diffuse reflectance spectroscopy (DRS) methods. Applying the Kubelka-Munk model on DRS results, the band gap energies of 2.09, 3.5, and 2.07 eV were obtained for BiOI, (BiO)2CO3, and BiOI/(BiO)2CO3 samples. pHpzc values of 6.3, 10.1, and 8.1 were estimated for BiOI, (BiO)2CO3, and BiOI/(BiO)2CO3, respectively. After observing the boosted photocatalytic activity by the coupled system, the interaction effects of the influencing variables in SSZ photodegradation were evaluated via the response surface methodology (RSM) approach. The optimal RSM-run conditions were 8.5 ppm SSZ at pH 8, which contained 0.28 g/L of the BiOI/(BiO)2CO3 catalyst and 29 min illumination time, resulting in 87% SSZ photodegradation. The effects of some scavenging agents were also studied to elucidate the relative roles of the reactive species in the SSZ photodegradation by the proposed catalyst, that is, hydroxyl radicals ∼ photoinduced electrons > superoxide radicals ∼ photoinduced holes. The proposed catalyst retained good activity after 5 successive reusing runs.